Penciptaan Animasi Frame by Frame Sebagai Media Promosi Universitas Potensi Utama - Triadi Sya'Dian; Muhammad Ali Mursid Alfathoni (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is a creative project involving the production of an animated promotional advertisement for Universitas Potensi Utama using a soft-selling approach that emphasizes aesthetics and emotional resonance rather than explicit promotional messages. The creation process is based on Hannah Frank’s frame by frame theory, in which each frame is manually drawn to highlight smooth motion, visual expression, and cinematic nuance. The animation is designed using a looping technique in both visuals and audio, creating a seamless and uninterrupted repetition. The visual design employs a modern animation style with detailed shading and lighting techniques to evoke a warm and reflective atmosphere. A touch of artificial intelligence is incorporated through the use of SUNO AI to generate Lo-fi background music, enhancing the calm and repetitive mood of the animation. This study utilizes qualitative data collection techniques with a descriptive approach. The methods employed include participatory observation during the production process, semi-structured interviews with practitioners and target audiences, as well as visual analysis of the aesthetic and narrative elements within the work. The final result demonstrates that the frame by frame approach, supported by AI-generated music, successfully enhances the visual and emotional appeal of the animation, making it an effective yet subtle medium for educational institution promotion.